Age, Gender, and Crime in a Stockholm Birth Cohort to Age 64 - Carlsson, Christoffer (Journal of developmental and life-course criminology, 2021)
We study the criminal histories of 14,608 males and females in a full Stockholm birth cohort born in 1953 to age 64. Using an update of The Stockholm Birth Cohort Study data, we explore the amount of crimes recorded in the cohort before and after the advent of adulthood. We break down the age/crime curve into separate parameters, including onset, duration, and termination. Throughout, we utilize the large number of females (49%; n = 7 161) in the cohort, and compare long-term patterns of male and female criminal careers. Next, we focus on adulthood, and explore the existence and parameters of the adult-onset offender and its contribution to the overall volume of crime in the cohort. While crime peaks in adolescence, the main bulk of crimes in the cohort occurred after the dawning of adulthood. Nearly half of all male, and more than two-thirds of all female, crimes in the cohort occurred after age 25. In the case of violence, the majority of offences — around two-thirds for both genders — took place in adulthood. Around 23% of all males and 38% of all females with a criminal record in the cohort were first recorded for a criminal offence in adulthood. While a majority were convicted only once, a proportion of adult-onset offenders had a considerable risk of recidivism and repeated recidivism. These results suggest that quite a substantial proportion of the population initiate crime in adulthood, and that these offenders account for a nonnegligible proportion of adult crime.